MANAJEMEN PEMBINAAN CABANG OLAHRAGA ATLETIK DI PUSAT PENDIDIKAN DAN LATIHAN PELAJAR (PPLP) PROVINSI JAWA TENGAH - Rumini (Journal of Physical Education Health and Sport, 2015)
The purpose of this research is to know the influence of the traditional game of rounders repetition techniques to increase gross motor skills of children SLB N Ungaran mild mental retardation. The method used in this study is the experimental method. This research is pretest posttest One Group Design. Methods of data analysis using the t test. Population and sample is a random sample of mild mental retardation children SLB N Ungaran totaling 7 children. All samples were given treatment repetition rounders game techniques.Gross motor research results with the t test there is the influence of the average results of a calculation using a mild mental retardation child hypothesis tests to run 1:43 (pre-test) and 2:57 (post-test), running 1:43 (pre-test) and 2:57 (post-test) , throws 1:29 (pre-test) and 2.71 (post-test), capturing 1:43 (pre-test) and 2:43 (post-test), hit 1:29 (pre-test) and 2:14 (post-test). Aspects that there is no influence, namely jumping 1.71 (pre-test) and 1:57 (post-test), jump 1:43 (pre-test) and 1:29 (post-test), kicking 1.71 (pre-test) and 1:29 (post-test) , In addition to every aspect of the average in the overall gross motor tests increased by an average of 1:44 (pre-test) and 2:07 (post-test). The conclusions in this study are repetition baseball game techniques affect the increase in gross motor skills mild mental retardation children SLB N Ungaran